APLIKASI PENYEBARAN INFORMASI FIKNET (FIK NEWS UPDATE) BERBASIS ANDROID - Muhammad Aldena Herdiputra (2021)
Simultaneously with the outbreak of the COVID 19 pandemic, UPN "Veteran" Jakarta stipulates distance learning, in which all teaching and learning activities are converted into online methods. Likewise with the dissemination of information to the academic community of the Faculty of Computer Science UPN "Veteran" Jakarta, but unfortunately the facilities and infrastructure at UPN "Veteran" Jakarta are not sufficient enough so that the dissemination of information is not conveyed equally. To solve this problem the author build an Android Application because the FIK academic community more often uses smartphones than computer to looking for news. In addition, this application can provide notifications about the latest information expected that he latest information about the Faculty of Computer Science UPN "Veteran" Jakarta will never be missed. The development of the application used the Waterfall method base on Android user interface.